Demir çelik endüstrisinde toz kömür ve karışımları enjeksiyonunun çevresel etkisinin incelenmesi - Koyunoğlu, Cemil (Lisansüstü Eğitim Enstitüsü, 2021)
Yüksek fırında kok tüketimini ekonomik sebeplerden ötürü azaltmak üzere geliştirilen toz kömür enjeksiyon teknolojisi, faydalarla birlikte bazı sorunları da beraberinde getirmektedir. Bu güncel sorunlardan önemli olanı, yüksek toz kömür enjeksiyonu nedeniyle kömürün yanma kalitesinin düşmesi ve yanmayan kömür parçacıklarının kok yatağı geçirgenliğini bozmasıdır. Hem maksimum toz kömür enjeksiyonunun sağlanması hem de düşük emisyon kaygıları nedeniyle yanma rejiminin iyileştirilmesi gerekmektedir. En önemli beklentiler, yanma alev kararlılığının sağlanması gibi yanma kalitesini arttıracak önlemler olmaktadır. Yanma kalitesinin arttırılması için yanma koşullarının iyileştirilmesi gerekmektedir. Hesaplamalı akışkanlar dinamiği yöntemi ile çalışan ANSYS-FLUENT çözümü, bu amacı kolaylaştıran önemli bir araçtır. Ayrıca yakıt türünün geliştirilmesi (ön işlemden geçirme, uçuculuğu yüksek külü düşük bir biyokütle ile veya iyileştirilmiş bir kömür ile karıştırarak yakma vb.) de diğer bir yöntem olarak demir çelik endüstrisinde tercih edilen alternatiflerdendir. Tez çalışmasında, yüksek fırında toz kömür yakılmasını simüle eden bir model geliştirilmiştir. Bu model ANSYS-FLUENT paket programı kullanılarak geliştirilmiştir. Modelin doğrulanmasında, literatürden yararlanılarak, pilot ölçekli bir toz kömür enjeksiyon sisteminde (EUR8544 projesi) yapılmış deney sonuçları kullanılmıştır. Geliştirilen ANSYS FLUENT ön-karışmasız yakma model sonuçları bu deneylerle karşılaştırılmıştır. Yapılan karşılaştırma, model ile deneysel proje sonuçlarının önemli ölçüde birbiri ile uyumlu olduğunu göstermektedir. Doğrulanan model yardımıyla optimizasyon çalışması yapılarak, yanma koşullarındaki iyileşmeler tespit edilmiştir. Modelde ve deneyde belirlenen sıcaklık dağılımları karşılaştırmasına göre, ölçülen ve hesaplanan değerler iyi bir uyum içindedir. O2 gaz çıkış yüzdesi dağılımında simülasyonla hesaplanan oksijen yüzdesi biraz daha yüksektir. Yanmanın yoğun olduğu bölgede CO oranı hesapta çok daha yüksek görülmektedir. CO2 oranı deney ve hesapta yaklaşık %14 civarında salınmaktadır. Uçucu çıkış hızı dağılımına göre ölçülen ve hesaplanan değerler iyi bir uyum içindedir. Yanabilen kömür (char) yanma hızı dağılımına göre ölçülen ve hesaplanan değerler önemli ölçüde uyumludur. Sonuç olarak yanma kalitesinin artması için, toz kömür enjeksiyonunun yakma havası ile buluştuğu enjektör çıkışında hava ile birlikte yoğun bir şekilde karışmasının zorunlu olduğu görülmektedir. Kok beslemesi sırasında, yüksek fırınının üstünden beslenen havanın yarattığı basıncın fırında dengelenmesi ve kömür yanma veriminin hesaplanması için, tüyerden yakma havasının kömür ile birlikte giriş hızının ortalama 200 m/s olduğu görülmüştür. Tüyerden YF'ye giren toz kömür parçacıklarının modellenen yanma geometrisinde hava ile etkin bir şekilde karıştığı bölgelerde yanmanın daha etkin olduğu söylenebilir. Nitekim CO2 oranının aynı bölgede fazla çıkması, etkin karışım bölgesinde, ideal yanmanın sağlandığının bir diğer göstergesidir. Kömür besleme debisi, üfleme hızı gibi parametreler modelde değiştirilerek, optimum koşulların belirlenmesine çalışılmıştır. Bununla birlikte model üzerinde kömür ve biyokütle karışımları çalışılarak, biyokütle kullanımı imkanları araştırılmıştır. Günlük ortalama 528 ton kok fırına şarj edilmektedir. Ham kömür ile marangoz talaşı karışımı halinde, toz kömür karışım miktarı günlük 134,7 ton olabilir. Bu da yaklaşık olarak günde 126,9 ton kok tasarrufu anlamına gelir. Ham kömür ile Mısır koçanı karışımı halinde ise, yaklaşık olarak günde 126,9 ton kok tasarrufu sağlanabilmektedir.

The recent increase in coke prices increases the need for powdered coal injection. Due to the increased use of TKE, the cost of maintenance or replacement is reduced when blast furnaces reach the end of their useful life. In addition, the implementation of tightened environmental standards by countries causes blast furnaces to face additional costs. TKE thus eliminates the high-cost requirement of the coke oven. It is not possible for TKE to completely replace coke in the YF operation. It is therefore very important to balance this change. While the TKE injection rate can be changed during the day, the product output from the plant cannot be reduced or increased at the same rate to avoid affecting the quality of the hot metal. The use of TKE also plays a very active role in reducing emissions from steel production. Pulverized coal injection technology, has been developed to reduce coke consumption in blast furnaces due to economic reasons. This technology brings some technical and environmental problems along with too. The most important of these current problems is that the combustion quality of coal decreases due to high dust coal injection and the non-combustible coal particles impair the permeability of the coke bed. The combustion regime needs to be improved both to ensure maximum dust coal injection and to reduce emission concerns. The expectation is to increase the combustion quality and meanwhile ensuring flame stability. To increase the combustion quality, the combustion conditions must be improved. ANSYS-FLUENT solution, which works with the computational fluid dynamics method, is an important tool that facilitates this purpose. Besides, the development of the burner (pre-treatment, burning by mixing high volatile ash with low biomass or mixing with treated coal, etc.) is another alternative in the iron and steel industry. Alternative methods are available for more efficient combustion of coal in the blast furnace and to prevent unwanted emissions at the end of combustion. The first of these is the coal improvement method, which is necessary to remove the volatile output rate of the coal earlier. In this regard, effective results were obtained by using the ant enzyme with the anaerobic digestion method. Previous extensive experimental work was used to implement the coal injection model in the blast furnace. The raceway in the blast furnace, which is the subject of this thesis, is the cavity created by the high-temperature blowing air in the blast furnace coke filler, in the region where it is blown. The length of the cavity is between 1-1.5 m. Combustion air blowing speed is around 200 m/s on average. In this region, the circulation time of a small particle with the gas is 10ms. In this case, the particle circulation time is much less than in conventional powdered coal boiler combustion chambers. The waiting time in the combustion chambers of the boilers is in the order of seconds. In the thesis study, the test results from an experimental study that was carried out in a pilot-scale pulverized coal injection system are used. The test results and the solutions made with the non-premixing combustion model were compared to verify the model. It has been concluded that both results are considered compatible with each other. So, using a developed simulation model, improvement is possible in the combustion conditions. In the model, the values measured and calculated according to the temperature distribution of the trial are in good harmony. The percentage of oxygen calculated by simulation is higher according to the O2 gas output percentage distribution. The CO percentage is much higher in the region where burning is intense in the experiments. The CO2 ratio is about 14%. The values measured and calculated according to the volatile output speed distribution and the combustion rate distribution are in good harmony. As in the experiments, different combustion results were obtained with three different coals in the model. According to the model results, Armco coal, which has the highest volatile matter content among the three different coals, burned more effectively. According to the model result, the current coal feed rate of Preussag coal is sufficient to provide combustion efficiency. O2 distribution is more homogeneous than the results of the normal Elk Creek combustion model since Elk Creek coal mixes more effectively with air in the furnace after grinding. Especially the low CO ratio towards the end of the furnace shows that the combustion efficiency is better than the normal Elk Creek. After grinding, the combustion air flow rate can be reduced a little more so that the Elk Creek coal is more ideally mixed with the air, so that there is no by-pass situation. Due to the increase in the contact surface of the coal with air after grinding, the volatile output was more intense in the middle parts of the furnace compared to the normal situation. The burning rate of coal (char), which can burn towards the upper left and end of the furnace, increased even more after grinding. As a result of most models, it is seen that the combustion air bypasses the furnace in the upper regions. An optimization study was carried out using the model to provide suitable feeding conditions. In addition, the possibilities of using biomass were investigated with the help of the model. In the optimization and biomass utilization studies, Azdavay charcoal and biomass mixtures (carpenter sawdust and corncob) were used as injection charcoal. Varying the parameters like coal feeding rate, airflow rate, etc. in the model, optimum conditions have been tried to define. Coal and biomass mixtures have been also studied and the possible use of biomass has been investigated. To balance the pressure exerted by the air fed from the top of the blast furnace during Coke feeding in the furnace and to calculate the coal combustion efficiency, the entry rate of the air burning from the feather together with the coal was found to be 200 m/s on average. It can be said that combustion is more effective in areas where pulverized coal particles entering YF from plumes are effectively mixed with air in the modeled combustion geometry. Excess CO2 in the same region is another indicator that ideal combustion is achieved. An average of 528 tons of coke is charged to the furnace per day. In the case of a mixture of raw coal and carpentry sawdust, the amount of powdered coal mixture can be 134.7 tons per day. This means approximately 126.9 tons of coke savings per day. In the case of a mixture of raw coal and corncob, approximately 126.9 tons of coke can be saved per day.
Investigation of environmental impact of pulverized coal and coal mixtures injection on the iron and steel industry
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Yanma mühendisliği; Combustion engineering; Çelik endüstrisi ve ticareti; Steel industry and trade; Kömür; Coal